Women’s Empowerment in Rara Asmoro Community: An Organizational Culture in Shadow Puppetry Performances - Ramonita, Latifa; Sukandar, Rudi; Widowati, Dewi (Humaniora: Journal of Indonesia Culture and Society, 2024)
The research discussed that the woman dalang was still not considered equal to male ones in shadow puppetry performances despite being developed in the Mataram Kingdom era. Various reasons caused this phenomenon, such as the audience's preferences for men's dalangs. To respond to this condition, an all-women's karawitan community, Rara Asmoro, emerged in Surakarta to give support to many women who love wayang arts. This community sought to embrace these women's potential to then jointly promote and strengthen their skills in the field of Javanese art and culture. The research attempted to analyze the organizational culture formed in the Rara Asmoro community as an effort to empower women in the Javanese wayang art. The research applied a qualitative descriptive method to obtain a complete picture of the problem by interviewing the leader of Rara Asmoro and its four members. It finds a significance of the leader in empowering its members, fostering their confidence and talents, and expanding their opportunities for networking within the Wayang world. The dynamics of the organizational culture in the community allow everyone to switch roles: as a dalang, as a karawitan player, and as a singer, which opens opportunities for all members to have added value and skills. Conflicts are always resolved in a democratic and respectful manner, in which the leader keeps all of her members close as a family. However, internally, concertive control has not been fully implemented in the organization as it is still centralized on the leader.